Influence of the Substituent on the Phosphine Ligand in Novel Rhenium(I) Aldehydes. Synthesis, Computational Studies and First Insights into the Antiproliferative Activity - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Gomez-San Martin, A; Gomez-San Martin, A; Aravena-Ponce, D; Aravena-Ponce, D; Muñoz-Osses, M; Muñoz-Osses, M; Llanos-Silva, L; Llanos-Silva, L (Royal Society of Chemistry, 2018)
Cyrhetrenyl aldehyde derivatives [(η5-C5H4CHO)Re(CO)2PR3] with R = methyl (Me, 2a), phenyl (Ph, 2b), and cyclohexyl (Cy, 2c) were synthesized by a photochemical reaction from the starting material [(η5-C5H4CHO)Re(CO)3] (1) and the corresponding phosphines. The complexes were fully characterized by FT-IR, 1H, 13C and 31P NMR spectroscopy, elemental analysis and mass spectrometry. The molecular structures of 2a-c have also been determined. Electronic structure calculations by TD-DFT and electrochemical studies are in sound agreement with the effect of the substitution of one carbonyl group by a phosphine ligand. Additionally, the antiproliferative activity of complexes 1 and 2a-c was studied on the human cancer cell lines HT-29 and PT-45 using an MTT assay. Out of all new compounds, only the triphenylphosphine derivative 2b exhibited pronounced cytotoxic effects on both cell lines, being ca. 1.5 times more potent than cisplatin. © 2018 The Royal Society of Chemistry.